Assessing how emergency and trauma ultrasonography is taught to medical students - Cruvinel Neto,José (2019)
ABSTRACT Objective To evaluate a method aimed at teaching ultrasound techniques to medical students in emergency settings. Methods A prospective study conducted with 66 sixth-year undergraduate medical students. Students participated in theory and practicing sessions with a 5-hour load; knowledge acquisition was assessed through pre- and post-course and 90-day tests. A questionnaire were distributed to the students after course completion for theoretical and practical knowledge assessment. Results Average pre-test grade in theoretical content evaluation was 4.9, compared to 7.6 right after course completion, and 5.9 within 90 days (p<0.001). Questions addressing technical aspects and image acquisition were mostly answered correctly; in contrast, questions related to clinical management of patients tended to be answered incorrectly. In practical evaluation, 54 students (81.8%) were able to correctly interpret images. Conclusion Ultrasound applicability and image acquisition techniques can be taught to medical students in emergency settings. However, teaching should be focused on technical aspects rather than clinical management of patients.